Impact of Nucleoporin-Mediated Chromatin Localization and Nuclear Architecture on HIV Integration Site Selection - Wong, Richard W. (J Virol, 2015)
It has been known for a number of years that integration sites of human immunodeficiency virus type 1 (HIV-1) DNA show a preference for actively expressed chromosomal locations. A number of viral and cellular proteins are implicated in this process, but the underlying mechanism is not clear. Two recent breakthrough publications advance our understanding of HIV integration site selection by focusing on the localization of the preferred target genes of integration. These studies reveal that knockdown of certain nucleoporins and components of nucleocytoplasmic trafficking alter integration site preference, not by altering the trafficking of the viral genome but by altering the chromatin subtype localization relative to the structure of the nucleus. Here, we describe the link between the nuclear basket nucleoporins (Tpr and Nup153) and chromatin organization and how altering the host environment by manipulating nuclear structure may have important implications for the preferential integration of HIV into actively transcribed genes, facilitating efficient viral replication.